APRESENTAÇÃO - Benite, Anna M. Canavarro; Vianna, Cintia Camargo; Figueiredo, Mércia Otaviana Barbosa de Sá; Silva, Configurações José Antonio Novaes da (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2019)
–